The Trichotomy of the Island. The Islanders, the Others and the Enemies on Pitcairn Island: An Analysis of Jutro przypłynie królowa by Maciej Wasilewski - Tęcza, Agata (Romanica Silesiana)
Pitcairn is inhabited by 56 people, largely the descendants of the mutineers aboard HMS Bounty. Despite being a British territory, the island never had a tight relationship with the Crown until 2004, when the British Empire had to settle a child molestation case that shook the whole island. In that case, 7 out of 14 men were accused of having sexual relations with minors during a timespan of almost 40 years. After the trial the island became divided into three camps — the Islanders, the Others, and the Enemies. Maciej Wasilewski’s book is a (literary) reportage of the author’s visit on Pitcairn after the trials of 2004. This article aims at analysing the three groups of islanders. By studying Wasilewski’s interviews with them, we try to examine the dynamics of this small and remote island and elaborate on the problematic division into “us” and “them” (the Islanders vs. Strangers and Others) that emerged in times of conflict and remains to this day. Key words: Pitcairn, Other/Otherness, Maciej Wasilewski, trichotomy, social division